Methyl Orange Absorption Using Chitosan from Shrimp Skin as an Adsorbent - Meriatna Meriatna; Sanda Mulia Utari; Rizka Mulyawan; Muhammad Muhammad; Zulmiardi Zulmiardi (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
In the coloring process, the textile industry generally uses synthetic (artificial) dyes, methyl orange (MO). In this study, the adsorption of methyl orange (MO) dye with chitosan was investigated in a series of batch laboratory studies. The adsorption equilibrium study used a MO solution with a concentration of 10 to 50 mg/L with an adsorbent weight of 3 g put into an Erlenmeyer and shaken until the adsorption reached an equilibrium condition. Meanwhile, the adsorption kinetics used a MO solution with an initial concentration of 10 and 20 mg/L with a volume of 100 mL with an adsorbent weight of 3 g and the solution was adjusted to pH 2. Effective operating parameters such as pH, initial concentration of dye (C0) and contact time at adsorption has been investigated. The results showed that the adsorption capacity of methyl orange (MO) dye from chitosan increased with an increasing acid content, and it was found that a solution of pH 2 was the optimal pH value for MO adsorption. The adsorption parameters for the Langmuir and Freundlich isotherms were determined by nonlinear regression and the equilibrium data were best explained by the Langmuir isotherm model, this was indicated by the high value of the correlation coefficient (R2), which was 0.9595. The maximum adsorption capacity was 0.1297 mg/g. Adsorption kinetics can be successfully applied to pseudo second-order kinetic models. The pseudo second-order model results show that the adsorption process is controlled by chemical sorption (chemisorption).